2016
DOI: 10.1007/s40620-016-0314-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment protocol with pulse and oral steroids for IgA Nephropathy after kidney transplantation

Abstract: In the absence of therapeutic guidelines for de novo or recurrent IgAN after kidney transplantation, our study reports that therapy with pulse and oral steroids for 6 months is associated with an improved renal function. Nevertheless, further randomized controlled studies in larger patient cohorts are necessary to establish the gold standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…As reported previously, the diagnosis occurred predominantly some years after transplantation [ 4 , 9 , 12 , 17 , 25 ]. The higher incidence of graft dysfunction at diagnosis was also found in other studies [ 7 , 9 , 17 , 20 ] and in the present study might reflect our center’s practice, in which mainly patients with nephrotic proteinuria and/or with graft dysfunction were referred for graft biopsy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As reported previously, the diagnosis occurred predominantly some years after transplantation [ 4 , 9 , 12 , 17 , 25 ]. The higher incidence of graft dysfunction at diagnosis was also found in other studies [ 7 , 9 , 17 , 20 ] and in the present study might reflect our center’s practice, in which mainly patients with nephrotic proteinuria and/or with graft dysfunction were referred for graft biopsy.…”
Section: Discussionmentioning
confidence: 90%
“…Data from the United States Renal Data Systems suggest that there are no benefits in choosing the initial immunosuppressive regimen based on the risk of recurrence [ 6 ]. After IgAN recurrence, some strategies have been reported, such as high-dose steroids [ 8 , 11 , 12 ], switching from azathioprine (AZA) to mycophenolate mofetil (MMF) [ 11 , 13 ], cyclophosphamide and plasma exchange [ 14 ], and rituximab [ 15 ], but the results do not support effective treatment outcomes. Blockade of the renin-angiotensin system (RAAS) appears to be effective in reducing proteinuria and blood pressure [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of steroids or other immunosuppressants in order to treat IgAN recurrence in the graft, although not well proved with clinical trials and prospective studies, may be required in selected patients [ 91 ]. Specifically, when biopsy-proven IgAN recurrence in the graft follows a rapidly progressive course, or nephrotic syndrome cannot be managed with conservative interventions, clinicians most often treat these patients according to the severity of the histopathology and the related recommendations for IgAN in the native kidneys [ 92–94 ]. Consequently, one approach for this group of patients could be therapy with high-dose glucocorticoids given orally or combining intravenous and oral administration for a few months, followed by a slow taper back to low doses, which are usually given to prevent rejection, carefully assessing individually the infection risk and adopting adequate prophylaxis strategies to counteract the possible metabolic and infectious side effects of steroids that may occur more frequently given the concomitant immunosuppressive therapy.…”
Section: Immunosuppressive Therapy In the Management Of Igan Recurrenmentioning
confidence: 99%
“…One retrospective cohort study reported by Messina et al . focussed on steroid pulse therapy . In this previous study, steroid pulse therapy in combination with oral steroids for 6 months for post‐transplant IgAN was associated with improved renal function, and no adverse effects were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to treatment strategies for primary IgAN in the native kidney, administration of renin–angiotensin–aldosterone system (RAAS) blockers is currently a recommended treatment strategy for post‐transplant IgAN . Although steroid pulse therapy is also a major therapeutic option for primary IgAN, it has not been studied fully in post‐transplant IgAN . In primary IgAN, the presence of glomerular crescents is associated with poor renal survival, but is thought to be reversible with immunosuppressive therapy .…”
mentioning
confidence: 99%